Curva de crescimento e acúmulo de matéria seca em couveflor cultivada em substrato - Gondim, Ancélio Ricardo de Oliveira; Prado, Renato de Mello [UNESP]; Correia, Marcus André Ribeiro [UNESP]; Alves, Adriana Ursulino; Cecílio Filho, Arthur Bernardes [UNESP]; Politi, Lucas Sanches [UNESP] (My University, 2011)
Aiming to evaluate the curve of growth and dry matter accumulation in cauliflower cv. Verona in commercial substrate for vegetables Plantmax ®, an experiment was conducted in a greenhouse at UNESP, Jaboticabal, SP. The experimental design was randomized blocks with six treatments, five replicates, each plot had a plan. The treatments consisted of sampling times (20, 30, 40, 50, 60 and 70 days after transplantation). Evaluations of plant height, leaf number, stem diameter, leaf area, dry matter of shoot, root and whole plant, and fresh weight of the inflorescence. Furthermore, calculated the relative growth rate (RGR) of leaves, stems, roots, flowers and whole plant, presented in g day-1 plant-1.The hybrid of cauliflower 'Verona' shows initial slow growth, stepping up from 30 days after transplantation. The maximum accumulation of dry matter per plant was 87g at 70 DAT, with the participation of sheets of 53.8%, stem 9.9%, 30.7% of inflorescence and root 6.5%. The cultivation cauliflower Verona in substrate showed high accumulation of dry Inflorescence.
Curve of growth and dry matter accumulation in cauliflower cultivated on substrate
Keywords: Absorption; Botrytis l; Brassica oleracea var; Growth; Plant nutrition